Education, communication and humanism in the journalism of Antoine de Saint-Exupéry - Morata Santos, Montserrat; Mayoral Sánchez, Javier; Rodríguez Martínez, Ruth (CIC. Cuadernos de Información y Comunicación, 2024)
This paper explores the educational and communicative values found in the journalistic production of the French writer Antoine de Saint-Exupéry. Values that are little known in communication and which in education have been erroneously reduced to the child environment. In both cases these values have their origin in the humanist thought of the author. It´s a personal conception that the writer reflected in his journalism and developed in his literature, especially in Le Petit Prince, a book that is an educational literary reference. This paper has been carried out with a qualitative methodology and based on the journalistic stories that Saint-Exupéry published in the French press. This article has a historical perspective, for the object of study, as well as current, since it investigates issues of interest at present from an interdisciplinary approach.